2011
DOI: 10.1002/ijc.25924
|View full text |Cite
|
Sign up to set email alerts
|

MED29, a component of the mediator complex, possesses both oncogenic and tumor suppressive characteristics in pancreatic cancer

Abstract: Mediator complex subunit 29 (MED29) is part of a large multiprotein coactivator complex that mediates regulatory signals from gene-specific activators to general transcription machinery in RNA polymerase II mediated transcription. We previously found that MED29 is amplified and overexpressed in pancreatic cancer and that MED29 silencing leads to decreased cell survival in PANC-1 pancreatic cancer cells with high MED29 expression. Here we further demonstrate decreased migration, invasion and colony formation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…Recently, mutations in the Med17 Mediator subunit have been associated with infantile cerebral atrophy (Kaufmann et al 2010), and a mutation in the Med23 subunit cosegregated with intellectual disability (Hashimoto et al 2011). Since oncogenesis results from gene disregulation, it is not unexpected that Mediator is involved in several cancers (Zhang et al 2005;Vijayvargia et al 2007;Firestein et al 2008;Gade et al 2009;Li et al 2010;Kuuselo et al 2011). Mediator has at least 25 subunits organized into four modules: head, middle, tail, and Cdk8 kinase modules.…”
mentioning
confidence: 99%
“…Recently, mutations in the Med17 Mediator subunit have been associated with infantile cerebral atrophy (Kaufmann et al 2010), and a mutation in the Med23 subunit cosegregated with intellectual disability (Hashimoto et al 2011). Since oncogenesis results from gene disregulation, it is not unexpected that Mediator is involved in several cancers (Zhang et al 2005;Vijayvargia et al 2007;Firestein et al 2008;Gade et al 2009;Li et al 2010;Kuuselo et al 2011). Mediator has at least 25 subunits organized into four modules: head, middle, tail, and Cdk8 kinase modules.…”
mentioning
confidence: 99%
“…MED23 was associated with lung cancers with hyperactive Ras signaling, and its expression levels was correlated with poor prognosis [17]. Many studies have suggested mediator complex subunits as oncogenic functional components on carcinogenic progress [18,19], although mechanisms related to these phenotypes are unknown. Since the mediator complex has been described as the end point of the cell signaling pathway, different transcription factors bind speci c mediator subunits to activate transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, scarce literature addressed the individual role of Mediator subunit in cellular migration. Recently, Kuuselo et al (2011) described that suppression of MED29, a Mediator component, decreased migration and invasion in PANC‐1 pancreatic cancer cells. Previously we reported that MED28 modulated EGF‐induced migration by phosphatidylinositol 3‐kinase/Akt/MMP9 signaling pathway in breast cancer cells (Lee et al, 2011).…”
Section: Discussionmentioning
confidence: 99%